2019
DOI: 10.1155/2019/9464608
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Fraction of Lannea microcarpa Engl. and K. Krause (Anacardiaceae) Trunk Barks Corrects Angiotensin II-Induced Hypertension and Endothelial Dysfunction in Mice

Abstract: Traditional remedies prepared from Lannea microcarpa leaves, barks, roots, and fruits are used to treat many diseases including hypertension. This study investigated whether oral administration of the ethyl acetate fraction of Lannea microcarpa trunk barks (LMAE) corrects angiotensin (Ang) II-induced hypertension in mice. Its effects on vascular function were specifically investigated. Experiments explored hemodynamic and echocardiographic parameters in vivo and vascular reactivity to acetylcholine (ACh) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…In this study, a slight but not significant decrease in total cholesterol and triglyceride compared to the Control group was observed at the dose of 1500 mg/kg bw suggesting that LAMIC might possessed a protective effect on the cardiovascular system. This result support a recent study in where ethyl acetate fraction from Lannea microcarpa is able to correct angiotensin II-induced hypertension and endothelium dysfunction in an in vivo model 15 . In addition, creatinine is a serum metabolite that the level could but not necessary indicate the physiology of the kidney 39,40 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, a slight but not significant decrease in total cholesterol and triglyceride compared to the Control group was observed at the dose of 1500 mg/kg bw suggesting that LAMIC might possessed a protective effect on the cardiovascular system. This result support a recent study in where ethyl acetate fraction from Lannea microcarpa is able to correct angiotensin II-induced hypertension and endothelium dysfunction in an in vivo model 15 . In addition, creatinine is a serum metabolite that the level could but not necessary indicate the physiology of the kidney 39,40 .…”
Section: Discussionsupporting
confidence: 92%
“…Lannea microcarpa is a plant widely used in Burkina Faso traditional medicine to treat several diseases including hypertension. Previous preclinical studies showed that extracts from this species have vasodilatory effects, antihypertensive properties and are powerful inhibitors of purified phosphodiesterases 5,15 . Others studies also indicate the presence of chemical groups compounds such as steroids, triterpenoids, coumarins, saponins, anthocyanins, tannins etc.…”
Section: Discussionmentioning
confidence: 99%
“…It can also reduce DG-PKC dependent myosin light chain kinase activity, and/or block ROCCs to decrease intracellular Ca 2+ and relax the mice aorta as reported previously [20,25,31]. In order to better determine the mechanisms of action on the muscle cell, the use of specific inhibitors would be necessary for future investigations.…”
Section: Discussionmentioning
confidence: 88%
“…Parasternal short-axis images were obtained in M-mode. Functional and structural modifications were evaluated as previously described [ 13 ].…”
Section: Methodsmentioning
confidence: 99%